SISTEM KEPEMILIKAN TANAH DALAM MASYARAKAT ADAT DAYAK DI KABUPATEN SINTANG - Sopian Sopian (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2018)
The Dayak Indigenous Peoples ownership system for land or land and growing crops on it lasts for a long time based on customary procedures and customs that apply and are in line with the laws and regulations that apply in this republic. The transfer of ownership, which ultimately resulted in the Dayak community being lost, ownership rights or management of the land or land they owned was thought to have occurred and even lasted, especially with the inclusion of large-scale plantation companies in this area. Land loss for Dayak people will sooner or later result in the fragility of food security resulting in weakening the potential for independent economic development. To deal with this reality Indigenous people must have a strategy of anticipating various possibilities, especially if there is a structured effort to defend their land or territory.